Do Generous Parental Leave Policies Help Top Female Earners? - Gozde Corekcioglu; Marco Francesconi; Astrid Kunze (Institute of Labor Economics (IZA), 2020)
Generous government-mandated parental leave is generally viewed as an effective policy to support women's careers around childbirth. But does it help women to reach top positions in the upper pay echelon of their firms? Using longitudinal employer-employee matched data for the entire Norwegian population, we address this question exploiting a series of reforms that expanded paid leave from 30 weeks in 1989 to 52 weeks in 1993. The representation of women in top positions has only moderately increased over time, and career profiles of female top earners within firms are significantly different from those of their male counterparts. The reforms did not affect, and possibly decreased, the probability for women to be at the top over their life cycle. We discuss some implications of this result to put into perspective the design of new family-friendly policy interventions.
Keywords: J18; J21; J22; J24; M14; 330; top earners; parental leave; women; regression discontinuity